An Analysis of Eight Grade Students’ Self-Efficacy Perception of Visual Mathematics Literacy and Their Actual Performance - Emre EV ÇİMEN and Eda AYGÜNER (Elementary Education Online, 2023)
The purpose of this research is to analyze the relationship between eight grade students` selfefficacy perception of visual mathematics literacy and their actual performance. The study was carried out with 56 female and 84 male, total 140 students selected from a public secondary school in Eskisehir. The declarative design of mixed method, which includes both quantitative and qualitative methods, was used in the study. For this purpose, the “visual mathematics literacy self-efficacy perception scale developed by Bekdemir and Duran and the “visual mathematics literacy actual performance test” which was developed specifically for this study were used to find out the relation between students’ scale points and actual performance test points. In addition, as qualitative method, a semi-structured interview was performed with 12 students whose scale scores and test scores were inconsistent. It was found that there was no correlation between perception scale scores and actual performance test scores. While students thought themselves as highly efficient in visual mathematics literacy, their actual performance did not reflect this perception. The reason behind this discrepancy was investigated with student interviews and it was concluded that it was not related to environmental or family factors, and that it was originated from the fact that students were not well aware of their self-efficacies as of the age group they belong to.